2005
DOI: 10.1002/ajpa.20081
|View full text |Cite
|
Sign up to set email alerts
|

New method for estimation of adult skeletal age at death from the morphology of the auricular surface of the ilium

Abstract: A new method for estimating skeletal age at death from the morphology of the auricular surface of the ilium is presented. It uses a multiple regression analysis with dummy variables, and is based on the examination of 700 modern Japanese skeletal remains with age records. The observer using this method needs only to check for the presence or absence of nine (for a male) or seven (for a female) features on the auricular surface and to select the parameter estimates of each feature, calculated by multiple regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 17 publications
0
58
0
1
Order By: Relevance
“…These results, in conjunction with significant sexual differences found in bias and absolute difference averages in the present study and the sexual differences of score distribution observed by Hens and Belcastro (2012), suggest that in further analysis when using the BuckberryeChamberlain method, the sexes should not be combined. In fact, these results are not surprising because Igarashi et al (2005) demonstrated that the mode of chronological change in the auricular surface differs between males and females. The mean absolute difference obtained herein when applying the SucheyeBrooks method is higher than that reported by Martrille et al (2007) in a North American sample and Hens et al (2008) in a documented Italian collection and lower than the results of Schmitt (2004) in a Thai skeletal collection.…”
Section: Discussionmentioning
confidence: 78%
“…These results, in conjunction with significant sexual differences found in bias and absolute difference averages in the present study and the sexual differences of score distribution observed by Hens and Belcastro (2012), suggest that in further analysis when using the BuckberryeChamberlain method, the sexes should not be combined. In fact, these results are not surprising because Igarashi et al (2005) demonstrated that the mode of chronological change in the auricular surface differs between males and females. The mean absolute difference obtained herein when applying the SucheyeBrooks method is higher than that reported by Martrille et al (2007) in a North American sample and Hens et al (2008) in a documented Italian collection and lower than the results of Schmitt (2004) in a Thai skeletal collection.…”
Section: Discussionmentioning
confidence: 78%
“…The auricular surface is an useful age indicator (Kobayashi, 1967;Lovejoy et al, 1985;Buckberry and Chamberlain, 2002;Osborne et al, 2004;Igarashi et al, 2005), as its decay is persistent in forensic and archeological contexts and it seems to cover wide ranges of ages up to elderly individuals (Storey, 2007). This study analyzed iliac auricular surfaces of adult individuals 15 years of age and above using two techniques: the original method of Lovejoy et al (1985) and the revised method of Buckberry and Chamberlain (2002).…”
Section: Adult Age Estimationmentioning
confidence: 99%
“…The features recorded include grain and density, macroporosity, billowing, striations, apex lipping, activity in the retroauricular area and transverse organization. Several scholars applied Lovejoy's method in different samples and noted that older individuals tended to be underaged, whereas the age of younger individuals was overestimated [13][14][15][16][17]. In addition, many studies found that the 5-year intervals proposed by Lovejoy et al [4] are unrealistically narrow [14,18].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, all variables are recorded in a binary scale, except for granulation and porosity (SSPIB), for which an ordinal system is used. Finally, Igarashi et al's [17] approach is based on the binary scoring (presence -absence) of 13 variables per individual, mainly concerning surface texture, porosity, granularity and hypertrophy.…”
Section: Introductionmentioning
confidence: 99%